Daily Optogenetic Stimulation of the Left Infralimbic Cortex Reverses Extinction Impairments in Male Rats Exposed to Single Prolonged Stress - Canto-de-Souza, Lucas [UNESP]; Demetrovich, Peyton G.; Plas, Samantha; Souza, Rimenez R.; Epperson, Joseph; Wahlstrom, Krista L.; Nunes-de-Souza, Ricardo Luiz [UNESP]; LaLumiere, Ryan T.; Planeta, Cleopatra Silva [UNESP]; McIntyre, Christa K. (Frontiers, 2021)
Post-traumatic stress disorder (PTSD) is associated with decreased activity in the prefrontal cortex. PTSD-like pathophysiology and behaviors have been observed in rodents exposed to a single prolonged stress (SPS) procedure. When animals are left alone for 7 days after SPS treatment, they show increased anxiety-like behavior and impaired extinction of conditioned fear, and reduced activity in the prefrontal cortex. Here, we tested the hypothesis that daily optogenetic stimulation of the infralimbic region (IL) of the medial prefrontal cortex (mPFC) during the 7 days after SPS would reverse SPS effects on anxiety and fear extinction. Male Sprague-Dawley rats underwent SPS and then received daily optogenetic stimulation (20 Hz, 2 s trains, every 10 s for 15 min/day) of glutamatergic neurons of the left or right IL for seven days. After this incubation period, rats were tested in the elevated plus-maze (EPM). Twenty-four hours after the EPM test, rats underwent auditory fear conditioning (AFC), extinction training and a retention test. SPS increased anxiety-like behavior in the EPM task and produced a profound impairment in extinction of AFC. Optogenetic stimulation of the left IL, but not right, during the 7-day incubation period reversed the extinction impairment. Optogenetic stimulation did not reverse the increased anxiety-like behavior, suggesting that the extinction effects are not due to a treatment-induced reduction in anxiety. Results indicate that increased activity of the left IL after traumatic experiences can prevent development of extinction impairments. These findings suggest that non-invasive brain stimulation may be a useful tool for preventing maladaptive responses to trauma.
Keywords: anxiety; lateralization and brain functions; memory; posttraumatic stress disorder; PTSD